BTEC Nationals - IT Practitioners Core Units for BTEC Nationals in IT and Computing - Anderson, Howard; Anderson, Howard; Yull, Sharon (Taylor & Francis, 2002)
Full coverage of all 6 core units for the new BTEC National specifications from Edexcel.BTEC Nationals - IT Practitioners is a new course text written specifically to cover the compulsory core units of the new BTEC Nationals specifications, which are replacing the current BTEC National Computing scheme in 2002.Students following all National Certificate and Diploma programmes within the new scheme will find this book essential reading, as it covers the core material they will be following through the duration of their course. Knowledge-check questions and activities are included throughout, resulting in a clear and straightforward text which encourages independent study. The coverage is designed to cater for students following a General, ICT Systems Support, or Software Development course. Answers to numerical problems are included, and further support material is available on the Newnes website.